1999
DOI: 10.1111/j.1151-2916.1999.tb01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Size on the Sliding Wear and Friction of Alumina at Elevated Temperatures

Abstract: The sliding friction and wear of three different grain-size aluminas were studied from room temperature through 1000°C. The coefficient of friction revealed two distinct regions of decrease with increased temperature, with a transition at ∼700°C. Below 700°C, the coefficient of friction decreased rapidly with increased temperature (∼10 −3 /°C). However, above 700°C, the decrease was more gradual (∼10 −5 /°C). This was believed to be related to a brittle-toductile transition at the wear surface. The coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…In most cases, a finer grain size of alumina leads to lower specific wear rates. 13,14 However, this phenomenon appears to be highly dependent on test configuration, as is indicated by other data showing a decrease in specific wear rate with increasing grain size. 15 Choosing a reactive sintering route for metal-ceramic composites has the advantage that the materials can be sintered pressureless to high densities.…”
Section: Introductionmentioning
confidence: 82%
“…In most cases, a finer grain size of alumina leads to lower specific wear rates. 13,14 However, this phenomenon appears to be highly dependent on test configuration, as is indicated by other data showing a decrease in specific wear rate with increasing grain size. 15 Choosing a reactive sintering route for metal-ceramic composites has the advantage that the materials can be sintered pressureless to high densities.…”
Section: Introductionmentioning
confidence: 82%
“…A large amount of experimental research work [1][2][3][4][5][6][7] has been done to investigate the friction and wear properties of ceramics, such as alumina and silicon carbide under different temperature [5], environmental media [6], and surface topography [7]. The conventional types of tribometer of pin-on-disk, roller on disk or plate on plate technique are usually used to carry out the friction test along unidirection or reciprocation.…”
Section: Introductionmentioning
confidence: 99%
“…The worn surfaces of coatings were covered with a discontinuous compact layer. The EDS analysis revealed that the compact layer contained large amounts of silicon but no nitrogen, suggesting that silicon nitride was oxidised and transferred to the worn surface of the coatings 7,18 . There were many cracks existing on the worn surface of the coatings and the compact layer was in the process of delamination as flake-like debris, due to the effect of the cyclic stress.…”
Section: Friction and Wearmentioning
confidence: 99%
“…The presence of adsorbed moisture and the formation of oxide films can decrease the wear of ceramics 13 . The wear rate of alumina-based ceramics increases with the temperature, increasing 12 up to 600 o C. Tetsuya 7 , et al found grain size also has an important effect on the wear resistance of alumina at elevated temperatures. Therefore, an interest has been shown by the researchers in the wear of plasma sprayed ceramic coatings at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation